Evaluation of the calcium humophosphate supplemented with phytase on phosphorus digestibility and performance in 21-day old broiler chickens - Varella, G. O.M. [UNESP]; Riveros, R. L. [UNESP]; Leme, B. B. [UNESP]; Ribeiro, B.; Poujol, M.; Sakomura, N. K. [UNESP] (Elsevier, 2025)
Phosphorus (P) is an essential nutrient for animal growth and maintenance. Calcium humophosphate is an innovative phosphate sources designed to enhance the bioavailability, while modulating of the gut environment. The objective of this study was to compare the performances response, apparent P digestibility, intestinal pH, and bone mineralization in broilers fed diets supplemented with calcium humophosphate compared to classical P source, monocalcium phosphate, and to assess their interactions with increasing levels of phytase. A total of 2800 one-day-old male broilers were randomly allocated to eight treatments with ten repetitions of 35 birds per pen. The treatments included two control diets supplemented with either calcium humophosphate or monocalcium phosphate as the inorganic P source, along with three levels of phytase supplementation (500, 1000, and 2000 FTU/kg). The control diets were formulated to meet the nutritional requirements based on Rostagno et al. (2017) recommendation, except for available P (0.53 %) and calcium (0.75 %), which were reduced to account for the contribution of 2000 FTU/kg phytase. The results shown that the birds fed with calcium humophosphate achieved higher (P < 0.05) body weight gain, reduced ileal pH, and improved bone mineralization compared to those fed monocalcium phosphate. No differences (P > 0.05) were observed between P sources for apparent ileal digestibility, feed intake, or duodenal and jejunal pH. These findings suggest that calcium humophosphate may work synergically with commercial phytases to enhance P utilization, leading to improve weight gain and modulation of upper gut pH.
Keywords: Growing chickens; Gut pH; Mineral nutrition; Mineralization